2022
DOI: 10.1002/adsc.202101365
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Alkynylation of Alkenes via C−H Activation for the Preparation of Conjugated 1,3‐Enynes

Abstract: A general palladium‐catalyzed method for the direct alkynylation of unactivated alkenes via C−H activation, was successfully developed, with the assistance of 8‐aminoquinoline. It is applicable to both internal and terminal unactivated alkenes with a broad functionality tolerance. This method shows good regio‐ and diastereoselectivity and provides an alternative approach for directing construct of conjugated 1,3‐enynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…With the assistance of a removable bidentate 8-aminoquinoline auxiliary, Pan and co-workers were able to regioselectively activate the β-C−H bonds of diverse β,γ-unactivated amides, enabling an expeditious route to a variety of conjugated 1,3enynes (Scheme 86). 185 Notably, a wide scope with respect to both terminal and internal unactivated aliphatic alkenes were smoothly coupled with bromoalkynes to generate the alkynylation products with overall high yields (58−79%). Bromoalkynes bearing TIPS, TBS, and TES groups were appropriate coupling partners, while other substituents such as phenylacetylene and methyl propionate were proven to be incompatible with the conditions.…”
Section: Alkenyl C−h Bond Functionalization Of Aliphatic Alkenes Cont...mentioning
confidence: 99%
“…With the assistance of a removable bidentate 8-aminoquinoline auxiliary, Pan and co-workers were able to regioselectively activate the β-C−H bonds of diverse β,γ-unactivated amides, enabling an expeditious route to a variety of conjugated 1,3enynes (Scheme 86). 185 Notably, a wide scope with respect to both terminal and internal unactivated aliphatic alkenes were smoothly coupled with bromoalkynes to generate the alkynylation products with overall high yields (58−79%). Bromoalkynes bearing TIPS, TBS, and TES groups were appropriate coupling partners, while other substituents such as phenylacetylene and methyl propionate were proven to be incompatible with the conditions.…”
Section: Alkenyl C−h Bond Functionalization Of Aliphatic Alkenes Cont...mentioning
confidence: 99%
“…Olefinic C­(sp 2 )–H alkynylation has been an active area of research in the past decade for the flexibility of introducing complex groups and constructing novel compounds. In the past decades, much progress has been achieved in the direct olefinic C­(sp 2 )–H alkynylation using noble transition metals such as Pd, Rh, Ru, and Au, and the participation of chelation-assisted systems with N , N -bidentate directing groups has been an ideal approach to achieve site-selective C–H bond functionalization. Recently, the development of direct C–H alkynylation catalyzed by 3d transition metals to construct C­(sp 2 )–C­(sp) bonds has been a promising direction because of their low price and lower toxicity. For instance, in 2015, Yi et al reported a nickel-catalyzed C–H alkynylation reaction between two kinds of inactivated C­(sp 2 )–H and triisopropylsilyl (TIPS)-substituted bromoalkyne, which is the first report on Ni-catalyzed C­(sp 2 )–C­(sp) bond formation via 8-quinolinyl-chelation assistance .…”
Section: Introductionmentioning
confidence: 99%
“…If the synthesis target involves 1,4-diaryl-1,3-enynes that have aryl groups placed in mutual syn positions (Figure 1b), cross-coupling [17][18][19]26,[36][37][38] is the only suitable synthetic route. Given the availability of procedures for the selective synthesis of silylated enynes (Figure 1c), the most convenient method for the preparation of (Z)-1,4-diaryl-1,3enynes is the protodesilylation of the silyl derivatives followed by Sonogashira coupling with aryl halides [39][40][41][42][43][44]. Alternatively, a one-step sila-Sonogashira coupling of the silylated enynes with aryl halides (E in Scheme 1) can be used [45].…”
Section: Introductionmentioning
confidence: 99%